From Molecular Mechanics to Nanocomposites: Engineering Polytetrafluoroethylene (PTFE) for High-performance Coating Applications - Neha Sahu; Rizwan Arif (International Journal of Advance in Molecular Engineering, 2024)
Polytetrafluoroethylene (PTFE) exhibits remarkable chemical inertness, hydrophobicity, antifriction, self-lubrication, and high-temperature resilience, making it an ideal polymer for various industrial applications, including coatings for medical implants, machinery parts, and corrosion-resistant structures. This study presents a comprehensive analysis of PTFE’s structural properties, focusing on helix reversals within its helical carbon-fluorine chains and their effects on mechanical behavior. The phase transitions of PTFE at temperatures from ambient to high (198°C and above) were analyzed, revealing significant insights into molecular conformations and their impact on thermal and mechanical stability. The performance of PTFE-based nanocomposites, such as TiO2-PTFE, was evaluated, demonstrating enhanced antibacterial and anticorrosive properties on stainless steel substrates. By comparing plasma-based coating techniques on carbon steel, this work emphasizes the unique tribological advantages of PTFE in reducing wear and friction in engineering applications. Future developments in PTFE applications in the technical and medicinal domains are made possible by these results.
Keywords: Antibacterial properties; helix reversals; nanocomposites; phase transitions; tribology